The impact of the arts in social work education: A systematic review. (March 2018) - Leonard, Kate; Hafford-Letchfield, Trish; Couchman, Wendy
Evidence on the effectiveness of arts-based approaches in professional education has been gathering momentum in the last decade embracing disciplines such as medicine, the allied professions, social work and social care. Key texts have emerged promoting the use of the arts in professional education and there have been some attempts to capture empirical evidence on its value. This paper reports on a systematic review of the current body of knowledge on the impact of the arts in social work education. We introduce the rationale for undertaking a systematic review and the methodology and approach used. We then discuss the three significant themes from our synthesis of the evidence reviewed. These were positioning social work practice through linking micro and macro thinking, the cultivation of leadership beyond verbal reasoning and art as pedagogy. The findings are discussed in the context of what the arts can offer challenges in social work education.